2020
DOI: 10.2399/ana.20.037
|View full text |Cite
|
Sign up to set email alerts
|

Morphological changes in temporomandibular joint dysfunction and effectiveness of different treatment methods

Abstract: Objectives: Temporomandibular joint dysfunction (TMD) results in changes in anatomical structures. The aim of this study was to examine the morphological changes using magnetic resonance imaging (MRI) and evaluate the effectiveness of different treatment methods in patients with TMD. Methods: 34 TMD patients (18–62 years of age) were randomly divided into two treatment groups. Group A (n=18) was subjected to dry needling (DN) and mobilization for 10 sessions, Group B (n=16) was instructed to use occlusal splin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 26 publications
0
6
1
Order By: Relevance
“…All masticatory muscle dimensions were significantly greater in males than females (P < 0.05), except for the width of the medial pterygoid muscle (P = 0.064), which suggested no sex differences. According In this regard, Duman et al (17) reported that the length and width of the masticatory muscles reduced dramatically in TMD patients, resulting in muscular atrophy, which might cause limited jaw mobility. Due to restricted jaw mobility, the masticatory muscles may no longer operate within their normal range, leading to their long-term atrophy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All masticatory muscle dimensions were significantly greater in males than females (P < 0.05), except for the width of the medial pterygoid muscle (P = 0.064), which suggested no sex differences. According In this regard, Duman et al (17) reported that the length and width of the masticatory muscles reduced dramatically in TMD patients, resulting in muscular atrophy, which might cause limited jaw mobility. Due to restricted jaw mobility, the masticatory muscles may no longer operate within their normal range, leading to their long-term atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…The medial pterygoid muscle was also evaluated using the coronal T1W sequence by measuring its height and width (Figure 2). Besides, the lateral pterygoid muscle (superior and inferior heads) was evaluated by measuring its height and length in the sagittal T1W closed mouth position (Figure 3) (17). To increase the reliability of measurements, they were repeated twice and reexamined for possible associated anatomical features in the sagittal T2W sequence.…”
Section: Image Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The temporomandibular joint (TMJ) is the joint between the mandibular condyles with the mandibular fossa and the articular tubercle of the temporal bone (Duman et al, 2020). TMJ is a ginglymoarthrodial joint formed by the glenoid fossa of the temporal bone and the mandibular condyle; it is a composite anatomical joint that allows both hinge motion (inferior joint between the articular disc and condyle) and gliding motion (superior joint between articular disc and temporal bone) (Moore et al, 2014;Baral et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A bicondylar joint is usually considered when two convex surfaces slide together, as it happens in TMJ and the knee joint (Sakul et al, 2019). However, the term "bicondylar" is used in multiple contexts in the current scientific literature reporting dissimilar forms and disagreements in the correct use of the term; while for some authors this term refers to two ellipsoidal condyles facing each other in the same joint (Sakul et al, 2019;Meyvaci et al, 2020), for others "bicondylar" refers to a TMJ is composed by right and a left condyle (Pai et al, 2019;Duman et al, 2020;Veras et al, 2021).…”
Section: Introductionmentioning
confidence: 99%